Gestión de residuos de construcción y demolición : hacia una integración en el Área Metropolitana de Buenos Aires - Mazzeo, Nadia Melisa (2024)
Urban built environment management encounters extensive environmental challenges, for example construction and demolition waste (C&DW) management. C&DW presents difficulties associated with their volume and weight, but also to cultural, economic, policy and governance issues. In order to plan a regional C&DW management strategy it is necessary to know how many, and which C&DW are generated, as well as the existing management practices; information which is not frequently available. This research aims to generate information about the dynamics that affect the management of the built environment in urban areas, specifically in its end of life, and suggest guidelines for improving their management. "Área Metropolitana de Buenos Aires" region (AMBA) was analyzed. In AMBA C&DW management entails similar and shared stakeholders, challenges, and opportunities. The most important challenges are the lack of a regional agreement at metropolitan scale and the absence of a traceability system that allows the C&DW movement quantification. A C&DW generation index was developed which can be used to diagnose C&DW generation in AMBA. It was also estimated that 77% of the C&DW that arrived at "Ciudad Autónoma de Buenos Aires" treatment plant were valorized and the rest of them where mainly good, recyclable materials and metals which can be treated if they were segregated at source. This segregation could be achieved through a traceability system which identifies the people responsible for this task and allow giving incentives. In conclusion, C&DW management in AMBA entails significant challenges, but also improvement and innovation opportunities. The implementation of the strategies and tools proposed in this study may allow a more efficient and sustainable C&DW management.